Modeling foundation species in food webs. Issue 12 (9th December 2013) - Baiser, Benjamin; Whitaker, Nathaniel; Ellison, Aaron M.
Abstract : Foundation species are basal species that play an important role in determining community composition by physically structuring ecosystems and modulating ecosystem processes. Foundation species largely operate via non‐trophic interactions, presenting a challenge to incorporating them into food web models. Here, we used non‐linear, bioenergetic predator‐prey models to explore the role of foundation species and their non‐trophic effects. We explored four types of models in which the foundation species reduced the metabolic rates of species in a specific trophic position. We examined the outcomes of each of these models for six metabolic rate "treatments" in which the foundation species altered the metabolic rates of associated species by one‐tenth to ten times their allometric baseline metabolic rates. For each model simulation, we looked at how foundation species influenced food web structure during community assembly and the subsequent change in food web structure when the foundation species was removed. When a foundation species lowered the metabolic rate of only basal species, the resultant webs were complex, species‐rich, and robust to foundation species removals. On the other hand, when a foundation species lowered the metabolic rate of only consumer species, all species, or no species, the resultant webs were species‐poor and the subsequent removal of the foundation species resulted in the further loss of species and complexity. This suggests that in nature we should look for foundation species to predominantly facilitate basal species.